2020
DOI: 10.24018/ejmed.2020.2.1.126
|View full text |Cite
|
Sign up to set email alerts
|

The progress towards achieving the UNAIDS ambitious viral suppression target among adults living with HIV in South-Western Nigeria

Abstract: Background: In sub-Saharan Africa where genotypic drug resistance testing is rarely performed and poor adherence is blamed for the inability to achieve viral suppression and treatment failure, programmatic approaches to preventing & handling these are thus essential. Hypothesis tested was antiretroviral therapy adherence effect on viral load outcome. This study was aimed at determining and monitoring HIV/AIDS disease progression using viral load to provide prognostic information and evaluate patients for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A 2017 study conducted in Western Nigeria discovered that 86.5 percent of the individuals experienced viral load suppression after thorough adherence counselling (7,8). The results of a 2017 study conducted in Western Nigeria on the 90-90-90 ambitious targets found that 787 (86.5 percent) of the individuals experienced viral load suppression of less than 1000 RNA copies per ml over the time of observation after thorough adherence counselling (7,8). This study examines the effect of EAC on viral load suppression.…”
Section: Introductionmentioning
confidence: 99%
“…A 2017 study conducted in Western Nigeria discovered that 86.5 percent of the individuals experienced viral load suppression after thorough adherence counselling (7,8). The results of a 2017 study conducted in Western Nigeria on the 90-90-90 ambitious targets found that 787 (86.5 percent) of the individuals experienced viral load suppression of less than 1000 RNA copies per ml over the time of observation after thorough adherence counselling (7,8). This study examines the effect of EAC on viral load suppression.…”
Section: Introductionmentioning
confidence: 99%